The Identity Politics of the Minority in Knitting the Constitutionality (The Legal review of Sunda Wiwitan Community of Cigugur, Kuningan, West Java) - Sarip Sarip (Universitas Lampung, 2017)
The Identity Politics of Sunda Wiwitan community, which nowadays is rated as a form of self-preservation to meet the economic needs of families, has been considered to get restraints from the state. The economic needs make the identity politics as a means to save oneself. The Identification card, which is known as KTP and in which there is a religion column, has created discrimination of the identity for the Sunda Wiwitan Community (KSW). The KSW still runs the obedience to the teachings of the ancestors but to save the economy, the status of the religion is willingly written to be recognized as other religions by the state. There is no other way to save the economic life for the sake of the family survival than to fill in the religion column with the state-recognized religions. The situation is certainly influential for the KSW against other identities such as marriage and education cards. The discussion uses the result that comes from the interviews and some literature. Then the result becomes something ideal for KSW to save themselves in the economic field by changing the identity on the ID card. It is the way from KSW in passing the identity politics to meet the economic needs while the other side becomes the weakness of the Indonesian national law that does not provide any space for KSW in order to have equal opportunity as the Indonesian citizen. Keywords: The Identity Politics, KSW, Constitutionality.